Hydroblaster - Miika J. Norvanto; Miika J. Norvanto; Miika J. Norvanto; Miika J. Norvanto; Pertti Huotari; Miika J. Norvanto; Antti Mäntysaari; Miika J. Norvanto (2005)
Tarina miehestä, joka haluaisi paremman elämän.